PERAN AGAMA DALAM MENGHADAPI PERUBAHAN SOSIAL TERHADAP GENERASI MILENIAL - Witria Wanda; Lorentius Goa (Jurnal Pelayanan Pastoral, 2024)
The millennial generation is a generation that easily adapts to all situations of the times, especially in social changes, this millennial generation is said to be a modern generation that easily adapts to new things. Social changes that occur today can also affect the millennial generation in all ways, both physical, social, cultural, and religious. So to keep the millennial generation carried away in the influence of positive social change, religion must also play a role in helping the millennial generation face existing social changes that may have a bad influence on them, it is hoped that religion can guide and maintain their faith, with the role of religion in their lives, the millennial generation can also bring a good influence for the development of the Church to adjust self with the social changes that are happening today. The purpose of this study is to determine the extent of the role of religion in directing the millennial generation in facing existing social changes, the method used in this study is quantitative method. Using data collection techniques from various related articles. The conclusion that can be drawn from this study is that religion plays an important role in helping the millennial generation face social changes that occur, religion helps the millennial generation in managing all aspects both social and religious, and with the role of religion to the millennial generation, the millennial generation has a good character and is able to develop its image and help the development of the Church.